Pre-trial detention in 20th and 21st Century Common Law and Civil Law Systems - Charret-Del Bove, Marion; Mourlon, Fabrice (Cambridge Scholars Publishing, 2014)
Pre-trial detention refers to the period when a person, after being arrested, is detained so as to determine the nature of the offences and the characterization of the charges. This notion is part and parcel of the legal proceedings of a criminal investigation and aims at striking a fragile balance between protecting the State and respecting individual freedoms. Lots of examples can be quoted to illustrate the various pre-trial detention modalities in common law and civil law traditions, incl ...